Design and evaluation of a 3D video system based on H.264 view coding - Kalva, Hari; Mayron, Liam M.; Christodoulou, Lakis (My University, 2006)
Recent advances in video compression and 3D displays have necessitated a further understanding and development of 3D video coding algorithms. The emergence of low cost autostereoscopic displays is expected to drive the growth of 3DTV services. This paper discusses key issues that affect the quality of 3D video experience on autostereoscopic displays. The characteristics of the human visual system can be exploited to compress individual stereo views at different qualities without affecting the perceptual quality of the 3D video. The H.264/AVC video coding algorithm was used to compress each view. We examine the bounds of asymmetric stereo view compression and its relationship to eye-dominance based on a user study. This paper also presents the design and development of a modular video player with stereoscopic and multi-view capabilities including a discussion of useful tools for accelerating the development and enhancing flexibility. The experimental results indicate that eye-dominance influences 3D perception and as a result will impact the coding efficiency of 3D video
Keywords: Digital video; Three-dimensional display systems; Computer graphics; Digital television; Television broadcasting; Visual communication; 3-D television